CORAK PENAFSIRAN JALĀLUDDĪN AL-SUYŪṬĪ: STUDI ATAS KITAB TAFSĪR JALĀLAYN - dan Adrika Fithrotul Aini, Syarwani (STAIN Kediri, 2015)
Tafsīr Jalālayn is one among other exegetical works commonly used in Indonesia, particularly in pesantrens. It is well-known that this work is relatively concise and straightforward that people can easily understand it. This paper attempts to discuss the authors of the work with a focus on Jalāluddīn al-Suyūṭī who completed and continued the work of Jalāluddīn al-Maḥallī. It will examine al-Suyūṭī’s types and methods in his interpretation work after the latter.Keywords: al-Suyūṭī, Tafsir al-Jalālayn, Tipologi Tafsīr